Penerapan Sustainable Development Goals Desa di Desa Perkebunan Sungai Parit Kecamatan Sungai Lala Kabupaten Indragiri Hulu - Muhammad Fardh’lu Rizky; Dadang Mashur (Jurnal Ilmiah Wahana Pendidikan, 2022)
Village Sustainable Development Goals are an integrated effort for economic, social, environmental, legal and community governance development at the village level. With the use of the 2021 village funds, which are prioritized to finance activities that support the achievement of the Village SDGs. This study uses the Visseren-Hamakers theory based on 3 aspects, namely economic aspects, social aspects, environmental aspects, and institutional aspects. The purpose of this study is to analyze how far the Sungai Parit Plantation village government has implemented the 18 Village Sustainable Development Goals in implementing development in the village. This study uses qualitative research methods with collecting techniques by observation, interviews, and documentation. The results of this study are that several village SDGs goals have been implemented in Sungai Parit Plantation village, but have not been 100% realized due to several problems, such as: Covid-19 pandemic, lack of understanding of the Sungai Parit Plantation village community towards SDGs, lack of quality human resources in carrying out programs. village SDGs program and intolerance among certain groups so that cooperation is difficult in the Sungai Parit Plantation village